Multiscale spectral discrimination of poorly-crystalline and intermixed alteration phases using aerial and ground-based ExoMars rover emulator data - Allender, E.J.; Cousins, C.R.; Gunn, M.D.; Mare, E.R. (Icarus, 2021)
A key goal of the ExoMars rover Rosalind Franklin is to analyze accessible hydrated mineral deposits using panoramic multiscale and multispectral imagery. We conducted a multiscale spectroscopic study on hydrothermally-altered basalt-hosted soils in the geothermal area of Námafjall in northern Iceland. Basaltic lavas here that have experienced first-order geochemical alteration produce a variety of cm-to-meter scale poorly-crystalline alteration patterns. The resulting unconsolidated sediments provide a natural analogue material to investigate intimately mixed soils comprising multiple poorly-crystalline hydrated phases. We use emulator instruments which replicate the capabilities of the ExoMars 2022 Panoramic Camera (PanCam), the Infrared Spectrometer for ExoMars (ISEM), and the CLose-UP Imager (CLUPI), alongside Raman, aerial, and X-Ray Fluorescence spectroscopic data to investigate how the detection of these mixed basalt-derived alteration phases varies as a function of spatial and spectral scale. We find soils at our study site to be comprised of unconsolidated sediments including Al-OH minerals, hydrated silica, and a variety of ferric oxides, all of which Rosalind Franklin will likely encounter along its traverse at Oxia Planum. We report on (i) the synergy and limitations between Mars rover instrument emulators as an integral part of mission preparation, (ii) how the mixed nature of these hydrothermally-altered soils affects resulting mineralogical interpretations at multiple scales, and (iii) geochemical inferences that can be made using ExoMars 2022 imaging emulators.